Application of a Silicone Sheet in Negative-Pressure Wound Therapy to Treat an Abdominal Wall Defect after Necrotizing Fasciitis - Shin, Jin Su (Arch Plast Surg, 2017)
Necrotizing fasciitis (NF) is an aggressive soft-tissue infection involving the deep fascia and is characterized by extensive deterioration of the surrounding tissue. Immediate diagnosis and intensive treatment, including debridement and systemic antibiotics, represent the most important factors influencing the survival of NF patients. In this report, we present a case of NF in the abdomen due to an infection caused by a perforated small bowel after abdominal liposuction. It was successfully treated using negative-pressure wound therapy, in which a silicone sheet functioned as a barrier between the sponge and internal organs to protect the small bowel.